Model Starlet, suatu Usulan untuk Mitigasi Bencana Longsor dengan Pendekatan Genetika Wilayah (Studi Kasus: Longsoran Citatah, Padalarang, Jawa) - Zakaria, Z. (Indonesian Journal on Geoscience, 2010)
DOI:Â 10.17014/ijog.v5i2.95Scientists, governments, employers, and communities have the same view on landslide disasters, that is the need to cut losses and to avoid loss of men. To deal with landslide disasters, an understanding of an area is required, especially for mitigation ( limitations and stabilization). To handle the slope - prone to landslides, an integrated approach is needed. A stabilization and integrated design (Starlet model) is a proposal in the handling landslide - prone slopes the integration among: (1) mapping system, (2) slope stability analysis, (3) simulation design of stable slope, and (4) guidance with environmental management along with monitoring. In addition, this also requires the participation of scientists, government officials, communities, and employers in facing these avalanche disasters. Citatah landslides formed a system with the largest to the smallest sizes that is a unity. The landslide in the western part of Pasir Pabeasan (Pasir Pabeasan - Citatah) is a complex one with the type of lateral spread. There are other landslides in the surrounding area, i.e: rock fall, rock toppling, slump, debris slide, and slide. The landslide shows the system and dimensions of landslide from the smallest to the largest one. Slopes in 22.29o to 44.28o should be noted because in general they are critical. They need stabilizations. Landslide area mapping system should consider the genetic region. A terrain genetic map will show areas of terrain genetic unit (TGU) which strongly supports the zoning maps of land movements. Based on terraingenetic unit (TGU), the Citatah landslides are common at symbol TGU 2331, 2232, locations between 2231 and 2331, locations between 2232 and 2331, and locations between 2233 and 2331, around the intersection of two faults (Cimandiri thrust fault cut by dextral strike - slip fault).